Wireless Scalable Video Coding Using a Hybrid Digital-Analog Scheme - Yu, Lei; Li, Houqiang; Li, Weiping (IEEE transactions on circuits and systems for video technology, 2014)
Wireless video broadcast/multicast and mobile video communication pose a challenge to the conventional video transmission scheme (which consists of separate digital source coding and digital channel coding). The reason is that the separate coding scheme is based on nonscalable coding design, and this unavoidably leads to cliff effect as well as limits the ability to support multiple users with diverse channel conditions. In this paper, we propose a novel wireless scalable video coding (WSVC) framework. Specifically, we present a hybrid digital-analog (HDA) joint source-channel coding (JSCC) scheme that integrates the advantages of digital coding and analog coding. Moreover, the proposed JSCC is able to broadcast one video with different resolutions to fit various devices with different display resolutions. Compared to most state-of-the-art video delivery methods, it avoids the staircase effect and realizes continuous quality scalability (CQS) on condition that the channel quality is within the expected range, and it has strong adaptability to channel variation with higher coding efficiency and better fairness among all receivers. Therefore, it is very suitable for wireless video broadcast/multicast transmission and mobile video applications. The experimental results show that for broadcasting/multicasting the videos with CIF and QCIF resolutions the proposed WSVC outperforms SoftCast (which is a new analog scheme) average 0.60-5.90 dB and 3.39-9.97 dB respectively, outperforms SVC+HM (which combines H.264/SVC codec and hierarchical modulation technique) average 3.87-9.13 dB and 0.27-10.47 dB respectively, and outperforms DCast (which is an up-to-date video delivery scheme) about 0.2-3.3 dB for the video with CIF resolution. The experimental results verify the effectiveness of our proposed WSVC framework.